Research at the IMF : Relevance and Utilization. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2013)
This evaluation report assesses research produced at the IMF between 1999 and 2008, focusing on the relevance and utilization of research to member country authorities, IMF staff, and other stakeholders. The report also examines the technical quality and management of research and offers recommendations for enhancing the relevance of research, improving the technical quality of analytical work, promoting openness to alternative perspectives, and improving the management of research.